Cost Recovery Rate Unit Hemodialisa Rumah Sakit ABC Tahun 2006-2008 - Supriadi Supriadi (Jurnal Vokasi Indonesia, 2013)
ABSTRACT. This research is motivated by the thought that Hemodialysis Unit at ABC hospital whichopened in 2005 , is a unit that produces , but in the determination of rates of hemodialysis services have notbeen done in detail , which includes only the cost component of operating costs of direct material regardless ofpersonnel costs , telephone and general logistics costs . The issue is whether income rates that have not beencalculated in detail to cover the costs incurred by the unit or how hemodilisia Cost Recovery Rate ( CRR ) ofthe Hemodialysis Unit.This study is a qualitative study using secondary data from monthly reports of severalABC RS unit to calculate total revenue and total cost Haemodialysis Unit. The data used is the data of2006,2007and2008.The results showed CRR Haemodialysis Unit 2006 = 41.69 % , 2007 = 71.36 % and2008 = 83.11 %.Based on the results obtained during the 3 years that CRR is still below 100 % , it indicatesthat the income earned Haemodialysis Unit for 3 years has not been able to cover the costs incurred for theoperation of the unit.Cost Recovery Rate Unit Hemodialisa Rumah Sakit ABC Tahun 2006-2008SupriadiVolume 1, Nomor 1, pp 78-9283Keywords : Cost Recovery Rate, income, rates